Dispositional Forgiveness and Mental Health and Well-Being: Adaptation of the Toussaint Forgiveness Scale in Georgia and Cross-Cultural Comparison with Poland - Sebastian Binyamin Skalski-Bednarz; Loren L. Toussaint; Nino Makhashvili; Mariam Razmadze; Paweł Dębski; Janusz Surzykiewicz (Religions, 2025)
Forgiveness is a multidimensional phenomenon that often functions as a disposition; it is closely linked to psychological well-being and religion/spirituality. However, no validated instruments have been available to assess forgiveness in the Georgian context. This study aimed to adapt the Toussaint Forgiveness Scale (TFS) for use in Georgia and to examine cross-cultural patterns of forgiveness and mental health among Georgian Orthodox Christians and Polish Roman Catholics. Methods: Study 1 (N = 321) validated the Georgian TFS using confirmatory factor analysis and assessed its convergent validity with perceived stress and religiosity. Study 2 applied structural equation modeling to analyze associations between forgiveness dimensions and mental health indicators in Georgian (n = 110) and Polish (n = 111) samples. Results: The Georgian TFS showed good psychometric properties. In both groups, self-forgiveness was associated with lower depressive symptoms; in Georgia, it also predicted higher quality of life. Forgiveness by God predicted reduced anxiety and depression in Georgia but not in Poland. Although path patterns varied, overlapping confidence intervals suggest no significant between-group differences. Conclusions: Forgiveness supports mental health across cultures, especially self-forgiveness. Its expression may show subtle, culturally nuanced patterns, though these require cautious interpretation.